Flower-like metal oxide composite as an efficient sulfur host for stable and high-capacity lithium-sulfur batteries - Chen, Xiudong; Zhang, Hang; Yan, Ping; Cao, Xiaohua; Zhan, Changchao; Liu, Jin-Hang (Journal of solid state chemistry, 2022)
The major factors of the sulfur host are the high sulfur loading, ability to relieve the volume change, inhibition of the shuttle effect and electric conductivity for lithium-sulfur (Li–S) batteries. To improve the electrochemical performance of Li–S batteries in terms of specific capacity and steady cycling, a significant amount of time and effort has been paid to investigate in the search for new hosts. Because of their capability to prevent the shuttle effect and control the deposition of lithium sulfides, metal oxide materials have been the subject of substantial research and development in relation to their application as sulfur hosts in Li–S batteries. In this study, an advanced type of lithium-sulfur battery called a NiO–ZnO composite was used as a suitable sulfur host (NiO–ZnO/S). A high initial reversible capacity of 1326 mAh g−1 was achieved in NiO–ZnO/S at 0.1C, and the sulfur loading was 73.8 ​wt%. In addition, a great improvement in cycling stability in NiO–ZnO/S (77.6% capacity retention was maintained after 400 cycles at 0.2C) and rate performance (662 mAh g−1 at 5C) were achieved, benefiting from the strategy of anchor function from metal oxide composite (strong adsorption via physical and chemical interactions) and the unique flower-like structure of NiO–ZnO (relief of the volume change). Flower-like metal oxide composite (NiO–ZnO) is successfully synthesized by simple hydrothermal method and high temperature annealing and exhibits good electrochemical performances as a sulfur host for lithium-sulfur batteries. [Display omitted] •Flower-like metal oxide composite (NiO–ZnO) is successfully synthesized.•The synergistic effect improves the cycling performance of the electrode.•The NiO–ZnO/S composite as a cathode for lithium-sulfur batteries delivers high and ultra-stable cycling performance.